(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Photosystem II (PSII) is a multi-subunit protein complex embedded in the thylakoid membrane of chloroplasts, playing a crucial role in oxygenic photosynthesis. This complex catalyzes the light-dependent oxidation of water, generating oxygen and providing electrons for the photosynthetic electron transport chain. Understanding the biochemical properties of PSII is essential for elucidating the intricate mechanisms of photosynthesis and exploring its potential for bioenergy applications